Comparação dos efeitos do Flunixin Meglumine, Firocoxib e Meloxicam no controle da inflamação após orquiectomia em equinos - Gobbi, Francielli Pereira (2018)
The objective of the present study was to evaluate and compare the analgesic and antiinflammatory act ion of flunixin meglumine, firocoxib and meloxicam in horses after orchiectomy through clinical - laboratory evaluation. Were evaluated 18 uncastrated horses of different races, with 4.99 ± 2.63 years of age and 790.62 ± 110.46 lb of body weight . According t o the drug used after castration, the animals were randomly assigned to three experimental groups with six animals each: GFM= flunixin meglumine, GF = firocoxib and GM = meloxicam. Samples of blood and peritoneal fluid were collected before (T0 ) and after orchiectomies (1, 3, 6, 9, 12, 24, 48, 72 and 120 hours ). The Peritoneal fluid, obtained through abdominal puncture, was submitted to physical - chemical analysis and blood samples obtained through jugular puncture, erythroleukogram and evidence of renal, he patic and muscle functionability. The results were submitted to descriptive statistical analysis and the means were compared by the “SNK” test at 5% of probability. After the orch iectomies the animals of the GF presented t achycardia and those of the GM tac hycardia and hyperthermia. Neutrophilic leukocytosis was observed in GFM, GF and GM animals and monocytosis in GFM and GM animals. The serum prot einogram of the three groups (GFM, GF and GM) revealed hypoproteinemia and the seric activity of the GGT enzyme activity showed a decrease in the values in the GFM, GF e GM. The values of AP were higher in GF when compared to GFM and GM. As for the AST concentrations, GM animals presented higher values than GFM and G F . There was also an increase in the seric activity of CK enzymes (T24, T 72 and T68) in the GFM, GF and GM animals. GI and GII animals had higher ur ea values compared to GM (T0, T72 and T20 ) and, in relation to creatinine, GM presented higher values than GFM and GF at all times evaluated in the postoperative period. The stain ing of the peritoneal fluid before the orchiectomies (T0) ranged from yellow - straw to yellow - gold, clear in the GFM, GF and GM groups and straw - yellow, red, amber and gold - yellow with turbidity levels ranging from clear to cloudy the orchiectomies. In the peritoneal fluid, an increase of the total protein was observed, AST and GGT increased in the GFM, GF and GM groups and of the AP enzymes from the GM animals. This is an acute phase response by determining the concentration of acute phase proteins (PFAs) i n blood serum and peritoneal fluid. The proteins ceruloplasmin, transferrin, albumin, haptoglobin and a 1 - acid glycoprotein were identified. There was increase of Cp, Hp, Tr, Alb and AGP in the animals of the three groups (GFM, GF, GM). In the comparison bet ween groups, the Cp and Tr values in the blood and LP of GM animals were higher than GFM and GF . For the variable Alb the GF animals sh owed higher values than the GFM and GM animals in all the evaluated moments. The flunixin meglumine and the firocoxib showed a superior action in relation to meloxicam. The orchiectomy triggers an inflammatory reaction in horses and the proteinogram can be used to diagnose and monitor postoperative complications